Improvement of bioethanol production from rice husks - Arismendy Pabón, Ana María (2020)
This work aimed to compare the production of bioethanol from rice husk through simultaneous hydrolysis and fermentation process (SSF) with that through hydrolysis followed by fermentation process (SHF). The raw material was pretreated under mild conditions with sodium hydroxide. Initially, the influence of particle size was evaluated in the enzymatic hydrolysis of pretreated milled and unmilled husk. Subsequently, the efficiencies of Saccharomyces cerevisiae IMR 1181 (SC 1181) and Saccharomyces cerevisiae IMR 1507 (SC 1507) yeasts were compared using the SSF process. Finally, the SSF and SHF processes were compared using the SC 1181 yeast. Although a little more glucose was generated using ground husk (36.6% vs. 35.5%), grinding costs have to be also considered. The SC1507 yeast performed best at all times. The bioethanol yields for SHF and SSF with SC 1181 were of 35.3% and 38.2%, respectively. Maximum yields in SSF were of 43.9% for SC 1507 and 38%for SC 1181.